Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1016/0741-5214(94)90229-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute arterial thrombosis associated with total knee arthroplasty

Abstract: Thrombectomy alone for acute arterial thrombosis associated with TKA generally is unsuccessful and associated with unacceptably high amputation rates. Dismal results without emergency bypass is due to underlying chronic occlusive atherosclerotic disease found in these patients and intimal plaque disruption that can occur with knee manipulation or tourniquet compression. Acute arterial occlusion after TKA is best managed by emergency arteriography and a femoroinfrageniculate bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 7 publications
(1 reference statement)
0
66
0
1
Order By: Relevance
“…3e9 Although rare, these complications deserve attention as they may have dire consequences, with mortality reaching up to 7%, amputation of up to 42%, as well as the development of other morbidities such as foot drop. 7 Injury may result in arterial occlusion, laceration, or both. Thrombotic occlusion is caused by an indirect mechanism such as joint manipulation or tourniquet application and presents with limb ischemia.…”
mentioning
confidence: 99%
“…3e9 Although rare, these complications deserve attention as they may have dire consequences, with mortality reaching up to 7%, amputation of up to 42%, as well as the development of other morbidities such as foot drop. 7 Injury may result in arterial occlusion, laceration, or both. Thrombotic occlusion is caused by an indirect mechanism such as joint manipulation or tourniquet application and presents with limb ischemia.…”
mentioning
confidence: 99%
“…Arterial injuries are a rare occurrence during elective orthopedic procedures, but the complications are significant, and the morbidity in terms of limb loss and long-term functional deficit can be devastating [2,14]. In addition to the intrinsic risk due to arterial proximity, Wilson et al [2] identified peripheral vascular disease (PVD) as a significant risk factor for arterial injury in patients undergoing elective orthopedic joint reconstruction.…”
Section: Discussionmentioning
confidence: 97%
“…The incidence in total knee arthroplasty is thought to be *0.03 to 0.05% [2,5,10]. It has been postulated that this complication may be generally underreported in the literature [7].…”
Section: Discussionmentioning
confidence: 99%